2016
DOI: 10.4049/jimmunol.1600019
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Trans-Signaling with the Superagonist RLI Promotes Effector/Memory CD8+ T Cell Responses and Enhances Antitumor Activity of PD-1 Antagonists

Abstract: Tumors with the help of the surrounding environment facilitate the immune suppression in patients, and immunotherapy can counteract this inhibition. Among immunotherapeutic strategies, the immunostimulatory cytokine IL-15 could represent a serious candidate for the reactivation of antitumor immunity. However, exogenous IL-15 may have a limited impact on patients with cancer due to its dependency on IL-15Rα frequently downregulated in cancer patients. In this work, we studied the antitumor activity of the IL-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 40 publications
(40 reference statements)
1
31
0
Order By: Relevance
“…Overall, in multiple models systems, regardless of formation, the sIL-15/IL-15Rα complexes have been shown to be significantly more potent than native IL-15 in both in vitro and in vivo studies [18,55,19,54]. Furthermore, these IL-15 agonists can also be applied to ex vivo stimulation of tumor-specific lymphocytes (TILs) and NK cells [67] or be engineered for cellular expression and viral vector expression but are not discussed herein for space consideration.…”
Section: Il-15 Super-agonistsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, in multiple models systems, regardless of formation, the sIL-15/IL-15Rα complexes have been shown to be significantly more potent than native IL-15 in both in vitro and in vivo studies [18,55,19,54]. Furthermore, these IL-15 agonists can also be applied to ex vivo stimulation of tumor-specific lymphocytes (TILs) and NK cells [67] or be engineered for cellular expression and viral vector expression but are not discussed herein for space consideration.…”
Section: Il-15 Super-agonistsmentioning
confidence: 99%
“…Whereas IL-15 alone increases IFN-γ production and PD-1 expression by CD8 T cells, the addition of IL-15 plus αPD-L1 decreased PD-1 expression and further increased IFN-γ secretion [47]. Combination therapy with IL-15 superagonists (RLI and ALT-803) and blocking antibodies against PD-L1 and CTLA-4 have also been shown to increase survival and reduce tumor growth in colon and glioblastoma murine tumor models, as compared to one of the treatments alone [67,61,62]. While αPD-L1 mAb alone was able to delay growth of colon carcinomas and rarely induced remission, combined treatment with αPD-L1 mAb plus RLI resulted in reduced tumor growth, longer survival, and tumor regression in 40% of mice [67,61,62].…”
Section: Using Il-15 In Combinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies have shown benefit of combining these two classes of drugs. 15 In this trial, we assess the safety of the combination of ALT-803 and nivolumab immunotherapy, and the anti-tumour activity of cytokine treatment in the treatment of NSCLC.…”
Section: Introductionmentioning
confidence: 99%